Basal ganglia‐cortical structural connectivity in Huntington's disease. Issue 5 (30th January 2015) - Novak, Marianne J.U.; Seunarine, Kiran K.; Gibbard, Clare R.; McColgan, Peter; Draganski, Bogdan; Friston, Karl; Clark, Chris A.; Tabrizi, Sarah J.
Abstract Huntington's disease is an incurable neurodegenerative disease caused by inheritance of an expanded cytosine‐adenine‐guanine (CAG) trinucleotide repeat within the Huntingtin gene. Extensive volume loss and altered diffusion metrics in the basal ganglia, cortex and white matter are seen when patients with Huntington's disease (HD) undergo structural imaging, suggesting that changes in basal ganglia‐cortical structural connectivity occur. The aims of this study were to characterise altered patterns of basal ganglia‐cortical structural connectivity with high anatomical precision in premanifest and early manifest HD, and to identify associations between structural connectivity and genetic or clinical markers of HD. 3‐Tesla diffusion tensor magnetic resonance images were acquired from 14 early manifest HD subjects, 17 premanifest HD subjects and 18 controls. Voxel‐based analyses of probabilistic tractography were used to quantify basal ganglia‐cortical structural connections. Canonical variate analysis was used to demonstrate disease‐associated patterns of altered connectivity and to test for associations between connectivity and genetic and clinical markers of HD; this is the first study in which such analyses have been used. Widespread changes were seen in basal ganglia‐cortical structural connectivity in early manifest HD subjects; this has relevance for development of therapies targeting the striatum. Premanifest HD subjects had a pattern of connectivity more similar to that of controls, suggesting progressive change in connections over time. Associations between structural connectivity patterns and motor and cognitive markers of disease severity were present in early manifest subjects. Our data suggest the clinical phenotype in manifest HD may be at least partly a result of altered connectivity. Hum Brain Mapp 36:1728–1740, 2015. © 2015 Wiley Periodicals, Inc.